Ghana: estudio sobre la alimentación y la nutrición urbanas en Accra - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
In the Accra Urban Food and Nutrition Study, IFPRI collaborated with the Noguchi Memorial Institute of Medical Research and the World Health Organization to examine the nature of urban poverty and how it relates to food insecurity and malnutrition in Accra. The main goal of the research project was to determine how the strategies employed by the urban poor to secure their livelihoods affected households’ food security, the care of children, and their resulting health and nutritional status. The report offers a description of the research focus, under Project Leader, Marie T. Ruel, some of the key findings, and recommendations for the program.; Urban Challenges to Food and Nutrition Security